Reduction of sympathetic inotropic response after ischemia in dogs. Contributor to stunned myocardium. - A A Ciuffo; P Ouyang; L C Becker; L Levin; M L Weisfeldt (The Journal of Clinical Investigation, 1985)
Eight open chest dogs underwent 25 min of coronary occlusion to determine whether brief myocardial ischemia disrupts the normal myocardial inotropic response to sympathetic nervous stimulation. If so, this could represent a mechanism contributing to postischemic myocardial dysfunction. Myocardial segment shortening was measured using ultrasonic dimension crystals before and after coronary artery occlusion and reperfusion. Left ansa subclavia stimulation and systemic norepinephrine (NE) infusion were used to test the myocardial inotropic response to neural stimulation and direct exposure to the sympathetic mediator, respectively. Before coronary artery occlusion, base-line preischemic segment shortening (12.5 +/- 1.6%) (SEM) increased during both sympathetic stimulation (20.2 +/- 1.4%) and NE infusion (19.7 +/- 1.1%). The control segment responded similarly. After ischemia and reperfusion there was no significant change in heart rate, aortic or left ventricular pressures, nor changes in control segment shortening. In contrast, shortening in the postischemic segment was markedly reduced compared to baseline (4.1 +/- 2.4%), and no longer responded to sympathetic stimulation (2.4 +/- 2.8%), while responsiveness to systemic NE was maintained (12.9 +/- 2.0%), P less than 0.001, which suggested injury to the sympathetic-neural axis during the period of ischemia. This reduced response to neural stimulation was persistent for up to 2 h after reperfusion. Left atrial or intracoronary infusion of bretylium tosylate, which releases norepinephrine from nerve terminals, resulted in an immediate inotropic response in the postischemic segment, which indicated that total depletion of NE from nerve terminals during the ischemic period had not occurred. Disruption of sympathetic neural responsiveness is likely a component of the mechanism of postischemic myocardial dysfunction whenever there is appreciable sympathetic drive to the heart.